Voltage- and light-controlled spin properties of a two-dimensional hole gas in p-type GaAs/AlAs resonant tunneling diodes - Galeti, H.V.A.; Galvao Gobato, Y.; Brasil, M.J.S.P.; Taylor, D.; Henini, M. (Springer, 2018)
We have investigated the spin properties of a two-dimensional hole gas (2DHG) formed at the contact layer of a p-type GaAs/AlAs resonant tunneling diode (RTD). We have measured the polarized-resolved photoluminescence of the RTD as a function of bias voltage, laser intensity and external magnetic field up to 15T. By tuning the voltage and the laser intensity, we are able to change the spin-splitting from the 2DHG from almost 0 meV to 5 meV and its polarization degree from − 40% to + 50% at 15T. These results are attributed to changes of the local electric field applied to the two-dimensional gas which affects the valence band and the hole Rashba spin–orbit effect.